Augmenting Students’ Speaking Skill Through Vlog as an Innovation in Learning - Ainan Salsabila (Syntax Idea, 2021)
In this era of globalization, technology media has become an important role that can be used in the world of education. Especially vlog can be used as content to explore creative potential for everyone to augment speaking skills. Vlog defines as the documentation using video component as a medium media to record that they want to talk about it. The purpose of this research article of the innovation in learning through vlog is to augment students’ confidence speaking skill in their classroom. The data of this research used case study in the form of descriptive analysis using qualitative research methods. Data collection techniques were collected by observation of eight grader graduate in SMP Darul Ulum Depok. The results of this research revealed that after the students conducted the vlog, the students successfully in the criteria points for improving speaking skill and they more enjoy in speaking performance. Besides, the use innovation through vlog can enhanced students’ fluency, pronunciation, vocabulary, and good performance.